The predictive value of serum ‌Ang-5 and SHLP1 levels for the risk and prognosis of complications in acute cerebral infarction patients: Serum ‌Ang-5 and SHLP1 levels in ACI - Zhang, Qian; Zhang, Xuehan; Wang, Shuli; Xu, Wenqiong; Wu, Lirong (Journal of Medical Biochemistry, 2026)
Objective To investigate the levels of ‌Survival of Motor Neurons Homolog Protein 1‌ (SHLP1) and serum Angiopoietin 5 (‌Ang-5) in patients with acute cerebral infarction (ACI) who also have brain-heart syndrome (BHS).Methods The concurrent group consisted of 208 patients with BHS-complicated ACI who were hospitalized between January 2023 and June 2025, whereas the nonconcurrent group consisted of 220 patients with simple ACI who visited the hospital during the same time frame. The serum levels of SHLP1 and ‌Ang-5 in the patients were assessed using an enzyme-linked immunosorbent assay. Pearson correlation analysis was used to investigate the relationships between the serum levels of ‌Ang-5 and SHLP1 in patients with ACI complicated by BHS and the following indicators: left ventricular ejection fraction (LVEF), cardiac troponin I (cTnI), N-terminal pro-brain natriuretic peptide (NT-proBNP), creatine kinase isoenzyme (CK-MB), and others. The diagnostic value of serum ‌Ang-5 and SHLP1 for BHS in patients with acute coronary insufficiency was evaluated using receiver operating characteristic (ROC) curves.Results Serum SHLP1 level and LVEF were lower in the concurrent group than in the nonconcurrent group, although serum CK-MB, NT-proBNP, cTnI, and ‌Ang-5 levels were greater in the concurrent group. Statistically, the differences were substantial (P
Keywords: Acute cerebral infarction; Angiopoietin 5; ‌Survival of Motor Neurons Homolog Protein 1; Diagnostic value